Combined Thermal Effect of Cool Roof and Cool Façade on a Prototype Building. (November 2015) - Pisello, Anna Laura; Castaldo, Veronica Lucia; Piselli, Cristina; Pignatta, Gloria; Cotana, Franco
Abstract: Recently, huge efforts were made to develop new passive solutions for optimizing building summer thermal-energy behavior. While cool roofs are well investigated, a lack of knowledge is detected about the benefits deriving from the combination of cool roofs and cool façades. This work aims at determining the thermal performance of innovative cool roofing membrane and cool façade painting when applied on a prototype building, through continuous monitoring. Additionally, sensitivity analysis is performed to investigate the thermal benefits of the coupled solutions. Results showed that the combined solutions generate significant passive cooling in terms of indoor operative temperature reduction.